2011
DOI: 10.1186/1472-6807-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the unique structural and physicochemical properties of the DraD/AfaD invasin in the context of its belonging to the family of chaperone/usher type fimbrial subunits

Abstract: BackgroundDraD invasin encoded by the dra operon possesses a classical structure characteristic to fimbrial subunits of the chaperone/usher type. The Ig-fold of the DraD possesses two major characteristics distinguishing it from the family of fimbrial subunits: 1) a distortion of the β-barrel structure in the region of the acceptor cleft, demonstrated by a disturbance of the main-chain hydrogen bonds network, and 2) an unusually located disulfide bond connecting B and F strands - the localization exclusively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Dr adhesins are a conserved family of gram negative bacterial adhesion proteins and they are assembled via chaperone-usher pathway (11). The biogenesis of Dr adhesins at the structural and molecular level is well known (1215). However, the mechanisms of interactions between Dr + E. coli and host cells that are crucial for bacterial pathogenesis are much less known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr adhesins are a conserved family of gram negative bacterial adhesion proteins and they are assembled via chaperone-usher pathway (11). The biogenesis of Dr adhesins at the structural and molecular level is well known (1215). However, the mechanisms of interactions between Dr + E. coli and host cells that are crucial for bacterial pathogenesis are much less known.…”
Section: Introductionmentioning
confidence: 99%
“…11 The biogenesis of Dr adhesins at the structural and molecular level is well known. [12][13][14][15] However, the mechanisms of interactions between Dr þ E. coli and host cells that are crucial for bacterial pathogenesis are much less known. Previous studies in our laboratory have shown that nitric oxide (NO) down-regulates the DAF expression in a dose-and time-dependent manner in an endometrial epithelial cell line.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the E subunit, two conserved cysteine residues forming a disulfide bond are important for stabilizing elements of the immunoglobulin fold of the Dr fimbriae. With regard to the DraD subunit (179), it has been reported that when the DraE subunit assembles, the DraD subunit localizes at the tip of the fiber (158,159,166,167,180). Jedrzejczak et al (181) have shown that the DraD subunit localizes at the tip, because it lacks a donor strand and as a consequence functions only as an acceptor.…”
Section: Afa/dr Adhesinsmentioning
confidence: 99%
“…It has been proposed by Le Bouguénec and coworkers (357) that the D adhesin subunits encoded by the dra, daa, and afa-1 to -3 operons function as an invasin for the entry of Afa/Dr DAEC into urothelial and bladder cells. DraD and AfaD adhesin subunits have been identified at the tips of Afa/Dr fibrils (167,180). AfaD protein, unlike the AfaE protein, was able to detach from the bacterium (28,168,169).…”
Section: Urinary Tract Infections and Pregnancy Complicationsmentioning
confidence: 99%